Trust and Trustworthiness of Friendship Relation In Yogyakarta and Makassar - Faturochman, Faturochman; Minza, Wenty Marina; Firmansyah, Muhammad Reza (Faculty of Psychology, Universitas Gadjah Mada, 2020)
Previous research conducted by the same authors found that personal attributes (benevolence, integrity, competence) and the relational attributes (closeness, support, and reciprocity) influence trust and trustworthiness. This paper aimed to test the proposed trust model on a new dataset while also testing for gender and regional differences. This research involved a collaboration between Universitas Gadjah Mada as a representative from Yogyakarta and Universitas Negeri Makassar as a representative from Makassar. There were 420 students that participated in this study; 157 (37.4%) men and 263 (62.6%) women. Regression analyses indicated that 42% of trust was formed by personal and relational attributes. Contrary to expectations, there were no differences in trust (p> 0.05) between females and males. However, there was a significant difference in trustworthiness (p0.05). This study provides an understanding on the importance of trust and trustworthiness in efforts to maintain pluralism, as a form of citizenship identity.